Analisis Pengaruh Endorsement dan Paid Promote terhadap Penjualan Online Shop dengan Teori Permainan - Silalahi, Restina; Sinaga, Marlina Setia (Journal of Mathematics, Computations and Statistics, 2023)
The growth of internet users gives the latest innovation in shopping, which is online shopping. Sellers can use paid promotions and endorsement strategies to represent the sales insights. This study examines the impact of paid promotions and endorsements on sales using game theory and variance analysis. Game theory is a mathematical approach to formulating conflict and competition that involves a variety of interests and has a desire to win. Then, variance analysis is used to test the significance of the influence some independent variables have on a dependent variable. The attributes used in this research are price, content quality, and influencer. The result for the best marketing strategies of paid promotion maximum profit is content quality of the paid promotions. Whereas, for the best marketing strategies for endorsement maximum profit is content quality of the endorsement. Then, the result of the varianceanalysis showed paid promotions and endorsements make a real difference to online store sales.